Climate policy and international capital reallocation - Marius Fourné; Xiang Li (Halle Institute for Economic Research (IWH), 2025)
This study employs bilateral data on external assets to examine the impact of climate policies on the reallocation of international capital. We find that the stringency of climate policy in the destination country is significantly and positively associated with an increase in the allocation of portfolio equity and banking investment to that country. However, it does not show significant effects on the allocation of foreign direct investment and portfolio debt. Our findings are not driven by valuation effects, and we present evidence that suggests diversification, suasion, and uncertainty mitigation as possible underlying mechanisms.
Keywords: F21; F36; F64; 330; capital flows; climate change policy; green investment; international asset allocation